2017
DOI: 10.1016/j.jsams.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Six-week transition to minimalist shoes improves running economy and time-trial performance

Abstract: Gradually introducing minimalist shoes over a six-week training block is an effective method for improving running economy and performance in trained runners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
0
20
0
2
Order By: Relevance
“…Furthermore, while we investigated the acute effects of distinct running shoes, it is possible that longer familiarization time to the running shoes would result in greater gains in both MP and TT. Consistent with this idea, Fuller and colleagues showed that gradual introduction of minimalist shoes during a 6-week training program improved RE and TT more than conventional shoes [23].…”
Section: Association Between Differences In Metabolic Power and Time ...mentioning
confidence: 90%
“…Furthermore, while we investigated the acute effects of distinct running shoes, it is possible that longer familiarization time to the running shoes would result in greater gains in both MP and TT. Consistent with this idea, Fuller and colleagues showed that gradual introduction of minimalist shoes during a 6-week training program improved RE and TT more than conventional shoes [23].…”
Section: Association Between Differences In Metabolic Power and Time ...mentioning
confidence: 90%
“…GET was determined using the V-slope method [ 31 ]. The ICT was chosen to eliminate factors inherent to treadmill testing such as different running technique and type of shoes that could cause measurement errors [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…First, enhanced performance; a lighter shoe improves running economy 11. Second, a change in running biomechanics.…”
Section: Why Change Shoes?mentioning
confidence: 99%